Non-sterilized fermentation of high optically pure d-lactic acid by a genetically modified thermophilic Bacillus coagulans strain. Issue 1 (December 2017) - Zhang, Caili; Zhou, Cheng; Assavasirijinda, Nilnate; Yu, Bo; Wang, Limin; Ma, Yanhe
Abstract Background Optically pured -lactic acid (≥ 99%) is an important precursor of polylactic acid. However, there are relatively few studies ond -lactic acid fermentation compared with the extensive investigation ofl -lactic acid production. Most lactic acid producers are mesophilic organisms. Optically pured -lactic acid produced at high temperature not only could reduce the costs of sterilization but also could inhibit the growth of other bacteria, such asl -lactic acid producers. Results ThermophilicBacillus coagulans is an excellent producer ofl -lactic acid with capable of growing at 50 °C. In our previous study, the roles of twol -lactic acid dehydrogenases have been demonstrated inB. coagulans DSM1. In this study, the function of another annotated possiblel -lactate dehydrogenase gene (ldhL3 ) was verified to be leucine dehydrogenase with an activity of 0.16 units (μmol/min) per mg protein. Furthermore, the activity of natived -lactate dehydrogenase was too low to support efficientd -lactic acid production, even under the control of strong promoter. Finally, an engineeredB. coagulans D-DSM1 strain with the capacity for efficient production ofd -lactic acid was constructed by deletion of twol -lactate dehydrogenases genes (ldhL1 andldhL2 ) and insertion of thed -lactate dehydrogenase gene (LdldhD ) fromLactobacillus delbrueckii subsp. bulgaricus DSM 20081 at the position ofldhL1 . Conclusions This genetically engineered strain produced onlyd -lactic acid under non-sterilized condition, and finally 145 g/L ofd -lactic acid was produced with an optical purity of 99.9% and a high yield of 0.98 g/g. This is the highest optically pured -lactic acid titer produced by a thermophilic strain.